2016
DOI: 10.28948/ngumuh.239358
|View full text |Cite
|
Sign up to set email alerts
|

Yapraktan Üre Uygulamasinin Farkli Armut (Pyrus Communis L.) Çeşi̇tleri̇nde Veri̇m, Meyve Kali̇tesi̇ Ve Bi̇oakti̇f Bi̇leşi̇kler Üzeri̇ne Etki̇si̇

Abstract: ÖZETBu çalışmada, üç farklı armut çeşidinde (Akça, Santa Maria ve Deveci) yapraktan üre uygulamasının verim, meyve kalitesi ve bioaktif bileşikler üzerine etkisinin belirlenmesi amaçlanmıştır. Tam çiçeklenmeden 30 ve 60 gün sonra üre içeren solüsyon (% 0 ve % 0,1 CH 4 N 2 O) tüm ağaçlara iki kez püskürtülmüştür. Kontrol uygulaması ile karşılaştırıldığında, verim, meyve ağırlığı ve geometrik ortalama çap, üre uygulaması ile önemli oranda artmıştır. Renk özellikleri, suda çözünebilir kuru madde, pH ve titre edil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The antioxidant activity was determined from 2.63 mmol kg -1 (A-01 and A-09) to 4.27 mmol kg -1 (A-23) in the FRAP assay. In the FRAP assay, the antioxidant activity was determined between the ranges 0.80-3.18 mmol kg -1 for pear varieties grown in Tokat region ( Küçüker et al, 2015) and 1.20-1.61 mmol kg -1 for local pear varieties from Posof region (Erbil et al, 2018). Azzini et al (2019) reported the antioxidant activity from 1.04 mmol kg -1 to 2.91 mmol kg -1 for Italian pear genetic resources.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity was determined from 2.63 mmol kg -1 (A-01 and A-09) to 4.27 mmol kg -1 (A-23) in the FRAP assay. In the FRAP assay, the antioxidant activity was determined between the ranges 0.80-3.18 mmol kg -1 for pear varieties grown in Tokat region ( Küçüker et al, 2015) and 1.20-1.61 mmol kg -1 for local pear varieties from Posof region (Erbil et al, 2018). Azzini et al (2019) reported the antioxidant activity from 1.04 mmol kg -1 to 2.91 mmol kg -1 for Italian pear genetic resources.…”
Section: Resultsmentioning
confidence: 99%
“…Weed control was performed regularly with a rotovator, many times each year. Growth, yield and quality parameters were done according to similar researches were done in such areas [2,29,40,47,62].…”
Section: Methodsmentioning
confidence: 99%
“…Ozturk and coauthors [46] reported that fruit weight was 190.36 g, fruit width was 64.25 mm, and fruit length was 107.27 mm in 'Santa Maria' pear cultivar. The fruit weight of 'Santa Maria' cultivar grafted on BA29 quince clone rootstock varied 147.5 -169.4 g [14], and recorded 140.0 -156.2 g by [29]. Reported that fruit weight was 183.00 -290.00 g and fruit width was 61.18 -81.86 mm in some pear cultivars grown in western Kosovo, and they reported that fruit weight was 195.18 g, fruit width was 65.21 mm, and flesh firmness was 4.96 kg/cm 2 in 'Santa Maria' cultivar [33].…”
Section: Pomological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideal rootstock selection for pear is a necessity in increasing the average fruit size for each cultivar (Pasa et al, 2017;Askari et al, 2019). Kucuker et al (2015) recorded that the weight of fruit varied according to cultivars and research years. And they reported that fruit weight in 'Santa Maria' grafted on BA29 ranged from 147.5 to 169.4 g. Erdem and Ozturk (2012) reported 140.00-156.20 g. Lepaja et al (2014) reported a fruit width of 61.18 to 81.86 mm and a fruit weight of 183.00 to 290.00 g. 'Santa Maria' fruit weight on different rootstocks in semi-arid conditions was reported 265.49 to 290.37 g (Ikinci et al, 2014).…”
Section: Pomological Characteristicsmentioning
confidence: 99%